Experience and prospects of innovative main roadways construction and maintenance technologies of new coal units of PJSC «Mine Management «Pokrovske» - Levit, Viktor; Kamenets, Viacheslav; Chebotenko, Denis (Technology audit and production reserves, 2023)
The object of research is the proven and promising innovative technologies for the construction and maintenance of main roadways in difficult mining and geological terms of the Private Joint Stock Company (PJSC) Pokrovske Mine Management of Metinvest-Pokrovskvugillia Group (Ukraine). The problem focused by the research is to ensure the effective innovative and modernized known technologies application of the main roadways construction and maintenance in new coal units. Namely, the roadways and chambers of the shaft yards, long horizontal and inclined main roadways to improve their operational state and technical and economic indicators of mining engineering and extracting operations. Based on the accumulated production experience, the results of the roadways state survey under construction and in operation, analysis of documentation and scientific and technical developments of world scientific institutions, recommendations for the investment projects implementation in terms of construction and mining technologies optimizing had formulated. The recommendations include the introduction of combined support systems adapted to mine management conditions, tunneling equipment of a new technical level of the world's best producers, methods of roadways maintaining by location in offloaded areas, and modern means of Geomechanic situation monitoring. The expected economic benefit of reducing the cost of roadways maintaining may be 20–25 %. The results are summaries of cooperation with the engineering and technical staff of Mine Management Pokrovske and Metinvest Holding. The results can be used in practice now, and more broadly after the victory and the start of economic recovery, including in Ukraine's mining sector.